The Role of Service Innovation and Service Quality in Improving Customer Satisfaction - Destya Salsabila Firmansyah; Yayan Firmansyah (PT. Maju Malaqbi Makkarana, 2026)
This research had the objective to determine the impact of innovation on service and service quality on customer satisfaction at the Baleendah Customer Service Unit of PT PLN (Persero). A causal quantitative method was employed. A sample of 125 respondents, all of whom had experienced service innovation, was selected for this study. The analysis was conducted using SmartPLS software, employing validity, reliability, and hypothesis tests to examine the data. The findings of this research indicate that the service innovation variable has a significant direct impact on the expected variable with a value of 0.036. Additionally, both service innovation and service quality significantly influence the customer satisfaction variable at the Baleendah Customer Service Unit of PT PLN (Persero), with an indirect effect of 0.173.